More Efficient Commitments from Structured Lattice Assumptions - Baum, Carsten; Damgård, Ivan; Lyubashevsky, Vadim; Oechsner, Sabine; Peikert, Chris (Security and Cryptography for Networks, 2018)
We present a practical construction of an additively homomorphic commitment scheme based on structured lattice assumptions, together with a zero-knowledge proof of opening knowledge. Our scheme is a design improvement over the previous work of Benhamouda et al. in that it is not restricted to being statistically binding. While it is possible to instantiate our scheme to be statistically binding or statistically hiding, it is most efficient when both hiding and binding properties are only computational. This results in approximately a factor of 4 reduction in the size of the proof and a factor of 6 reduction in the size of the commitment over the aforementioned scheme.